1976
DOI: 10.1111/j.1476-5381.1976.tb07651.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cholinoceptor Antiserum: Its Pharmacological Properties

Abstract: I Sera of rabbits immunized against a nicotinic receptor-rich fraction, obtained from the electric organ of Torpedo marmorata, were tested for their pharmacological activity on different in vitro preparations. 2 Sera containing antibodies against the nicotinic receptor blocked neuromuscular transmission in the phrenic-nerve hemidiaphragm preparation without affecting the muscle responses evoked by direct electrical stimulation. Complement inactivated sera were still active. Immune sera, incubated for 15 min wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This model, referred to as experimental myasthenia gravis, is based on the observation that the injection of purified acetylcholine receptor (AChR) produces muscular weakness and fatigue in several animal species (Patrick, Lindstrom, Culp & MacMillan, 1973; Sugiyama, Benda, Meunier & Changeaux, 1973;Lennon, Lindstrom & Seybold, 1975;Green, Miledi, Perez & Vincent, 1975 a; Green, Miledi & Vincent, 1975b;Tarrab-Hazdai, Aharanov, Silman, Fuchs & Abramsky, 1975;Granato, Fulpius & Moody, 1976;Ito, Miledi, Vincent & Newsom-Davis, 1978). Using conventional electrophysiological techniques it has been shown that neuromuscular transmission in immunized animals is severely impaired (Green et al 1975a, b;Lambert, Lindstrom & Lennon, 1976; Berti, Clementi, Conti-Tronconi & Folco, 1976;Sanders, Schleifer, Elderfrawi, Norcross & Cobb, 1976;Ito et al 1978; Lindstrom & Lambert, 1978). In addition, as in human myasthenia gravis, there is a decrease in the binding of a-bungarotoxin (a-BuTx) at muscle end-plates (Fambrough, Drachman & Satyamurti, 1973;Green et al 1975a;Ito et al 1978;Lindstrom & Lambert, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…This model, referred to as experimental myasthenia gravis, is based on the observation that the injection of purified acetylcholine receptor (AChR) produces muscular weakness and fatigue in several animal species (Patrick, Lindstrom, Culp & MacMillan, 1973; Sugiyama, Benda, Meunier & Changeaux, 1973;Lennon, Lindstrom & Seybold, 1975;Green, Miledi, Perez & Vincent, 1975 a; Green, Miledi & Vincent, 1975b;Tarrab-Hazdai, Aharanov, Silman, Fuchs & Abramsky, 1975;Granato, Fulpius & Moody, 1976;Ito, Miledi, Vincent & Newsom-Davis, 1978). Using conventional electrophysiological techniques it has been shown that neuromuscular transmission in immunized animals is severely impaired (Green et al 1975a, b;Lambert, Lindstrom & Lennon, 1976; Berti, Clementi, Conti-Tronconi & Folco, 1976;Sanders, Schleifer, Elderfrawi, Norcross & Cobb, 1976;Ito et al 1978; Lindstrom & Lambert, 1978). In addition, as in human myasthenia gravis, there is a decrease in the binding of a-bungarotoxin (a-BuTx) at muscle end-plates (Fambrough, Drachman & Satyamurti, 1973;Green et al 1975a;Ito et al 1978;Lindstrom & Lambert, 1978).…”
Section: Introductionmentioning
confidence: 99%